과학 교수 학습 방법에 관한 국내 연구 동향 및 이슈 - 강경희; Kang, Kyung Hee (과학교육연구지 : 경북대학교 과학교육연구소, 2010)
The purpose of this study was to analyze the trend of domestic studies related to science teaching-learning methods. We reviewed articles published according to year, method, subjects and topic. The methods reported commonly in science education books were extracted. Experiment, cooperative learning, and discussion were methods which had been researched widely. Experimental study of them was utilized most. And next content analysis, survey, and case study were utilized much. The most object of experimental study was middle school students. These reviewed papers showed effects which were related to science achievement, attitude, inquiry ability and self-efficacy. As a result of this study we should research to apply and develop science teaching-learning methods variously. We ought to enlarge research direction to analyze context which applies science teaching-learning methods to educational field by qualitative study. We should try to study effects of teaching-learning methods longitudinally and latitudinally. 이 연구의 목적은 과학 교수 학습 방법에 관한 국내 연구 동향을 분석하기 위한 것이다. 국내 학회의 학술지 6종에 게재된 논문들을 연도 방법 대상 주제에 따라 분석했다. 분석대상은 과학교육 분야 문헌들에서 공통적으로 제시하고 있는 방법들을 추출되었다. 분석 결과 과학 교수 학습 방법에 관한 연구들은 2000년 이후 지속적인 증가세를 보였다. 교수 학습 방법 중 실험, 협동학습, 토의가 많이 연구되었다. 이 세 가지 방법에 관한 연구들에서 가장 많이 채택하고 있는 연구방법은 실험연구로 나타났다. 다음으로는 내용분석, 조사연구, 사례연구 등의 순으로 나타났다. 세 가지 방법에 관한 실험연구는 중학생을 대상으로 한 것이 가장 많았다. 특히 실험연구를 통해 과학 성취도, 태도, 탐구능력, 자기효능감과 관련한 과학 교수 학습방법의 효과를 알아보는 것으로 나타났다. 이 연구의 결과를 근거로 볼 때 향후 과학 교수 학습 방법에 관한 연구는 다양한 방법들에 대한 적용 개발 연구 등이 이루어져야 할 것이다. 또한 질적 연구방법을 통해 교수 학습 방법이 실제 교육현장에 적용되는 맥락을 분석하도록 연구 방향이 확대될 필요가 있다고 생각된다. 그리고 다양한 학습자 집단을 대상으로 한 연구를 통해 교수 학습 방법의 효과를 종단적 횡단적으로 접근하려는 시도가 필요할 것이다.